The Microbiome of the Lower Respiratory Tract in Premature Infants with and without Severe Bronchopulmonary Dysplasia - Imamura, Takashi; Sato, Maki; Go, Hayato; Ogasawara, Kei; Kanai, Yuji; Maeda, Hajime; Chishiki, Mina; Shimizu, Hiromi; Mashiyama, Fumi; Goto, Aya; Momoi, Nobuo; Hosoya, Mitsuaki (American Journal of Perinatology, 2017)
Aim We determined whether the bacteria in the lower respiratory tract (LRT) in extremely premature infants with severe bronchopulmonary dysplasia (BPD) are different from those with nonsevere BPD.Study Design We conducted a retrospective study of extremely premature infants who were admitted to the neonatal intensive care unit of Fukushima Medical University Hospital, Japan between April 2005 and March 2014. We screened for the bacterial colonization of the LRT using tracheobronchial aspirate fluid.Results A total of 169 extremely premature infants were included. Overall, 102 did not experience severe BPD, whereas the remaining 67 experienced severe BPD. Corynebacterium species (Cs) were more frequently detected in the severe BPD than nonsevere BPD infants (p = 0.03). There were significant differences between infants with and without severe BPD in the duration of endotracheal ventilation (p = 0.00, odds ratio [OR], 1.03; 95% confidence interval [CI], 1.01–1.06), the duration of supplemental oxygen (p = 0.00, OR, 1.02; 95% CI, 1.01–1.03) before 36 weeks of postmenstrual age, and the frequency of sepsis after 7 postnatal days (p = 0.01, OR, 1.73; 95% CI, 1.18–2.54).Conclusion Cs are more likely to be present in the severe BPD infants with longer duration of endotracheal ventilation.
Keywords: bronchopulmonary dysplasia; Corynebacterium; extremely premature; infants; surveillance; tracheobronchial aspirate fluid